Mariana disaster (MG, Brazil): a perspective concerning the environmental, bioethics and human rights impact (Brazilian Journal of Health Research, 2022)
Introduction: Bioethics is embedded in ethical issues raised by medicine, life sciences and associated technologies in its application to human beings, allowing reflection on values and concepts ‒ life, quality of life, suffering, resilience, dignity, health and illness. Considering that in dams disasters the population loses part of its identity and that all environmental accidents present records of serious public health problems besides other consequences, the proposal involves collective health, the environment and society. Objective: To present a theoretical context about disasters; environmental impacts; Bioethics and Violated Human Rights, focusing on the origin of the disaster of Mariana, MG, main problems and challenges. Methods: A critical-reflective, descriptive exploratory study with a qualitative approach, related to environmental accidents in mining and the responsive focus of the Mariana, Minas Gerais disaster, on November 5, 2015. Results: It was verified that technological progress in a model of development that aims only at the production of wealth undoubtedly brings the increase of social, environmental, economic and individual risks. Conclusion: Tragedies occurring in tailings dams are announced, the Mariana disaster is not an isolated case. However, along with the disaster in Brumadinho, in the Metropolitan Region of Belo Horizonte, in early 2018, one of the biggest man in the mining sector, bringing up the discussion of the renewal process of the environmental license and the interface with the surrounding communities.
Keywords: Mariana, MG.; Man-made disaster; Mining; Public health; Bioethics